2017
DOI: 10.1039/c6sc02912d
|View full text |Cite|
|
Sign up to set email alerts
|

Inner-sphere vs. outer-sphere reduction of uranyl supported by a redox-active, donor-expanded dipyrrin

Abstract: The uranyl(vi) complex UO2Cl(L) of the redox-active diimino-dipyrrin anion, L– is reported and its reactions with inner- and outer-sphere reductants studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
104
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 70 publications
(110 citation statements)
references
References 62 publications
(51 reference statements)
6
104
0
Order By: Relevance
“…Upon deprotonation of HL to form KL,a ni ntense band at 654 nm appeared in the UV/vis spectrum ( Figure 5), and is similar, although red-shifted, to the HOMO-LUMO transition in related dipyrromethene compounds; [6] the band seen at 295 nm is indicative of reprotonation of KL and highlights its sensitivity to water. Oxidation of KL to the radical LC resulted in ac onsiderable hypsochromic shift of the lowenergy absorption band from 654 to 456 nm, which is explained by an increase in the SOMO(a)-LUMO(a)g ap, according to TD-DFT calculations,f rom 4.41 keV in KL to 5.41 keV in LC.I ncorporation of the dinuclear core in Cu 2 I 2 -(LC)leads to the appearance of additional absorption bands,in particular ab road absorption at 826 nm (765 nm in the calculated spectrum), mainly involving the SOMO(b)-LUMO(b)t ransition.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…Upon deprotonation of HL to form KL,a ni ntense band at 654 nm appeared in the UV/vis spectrum ( Figure 5), and is similar, although red-shifted, to the HOMO-LUMO transition in related dipyrromethene compounds; [6] the band seen at 295 nm is indicative of reprotonation of KL and highlights its sensitivity to water. Oxidation of KL to the radical LC resulted in ac onsiderable hypsochromic shift of the lowenergy absorption band from 654 to 456 nm, which is explained by an increase in the SOMO(a)-LUMO(a)g ap, according to TD-DFT calculations,f rom 4.41 keV in KL to 5.41 keV in LC.I ncorporation of the dinuclear core in Cu 2 I 2 -(LC)leads to the appearance of additional absorption bands,in particular ab road absorption at 826 nm (765 nm in the calculated spectrum), mainly involving the SOMO(b)-LUMO(b)t ransition.…”
mentioning
confidence: 86%
“…Accordingly,w eh ave shown that aN -donor-expanded dipyrrin ligand [5] is redox active and able to mediate sequential electron transfer to au ranyl(VI) center ( Figure 1). [6] Ligand-centered oxidation was also seen in Ni complexes of asimilar bis(phenolate)dipyrrin ligand, with the one-electron oxidation product characterized as aligand-centered radical. [6] Ligand-centered oxidation was also seen in Ni complexes of asimilar bis(phenolate)dipyrrin ligand, with the one-electron oxidation product characterized as aligand-centered radical.…”
mentioning
confidence: 99%
“…[5] Electron Localization Function (ELF) calculations were carried out using the TopMod suite. [6] Molecular orbital surfaces and electron densities from ELF calculations were exported as cubefiles, visualized in UCSF-Chimera [7] and rendered with the Pov-Ray raytracer program.…”
Section: Methodsmentioning
confidence: 99%
“…This calculated structure is different to that seen in the X-ray crystal structure of L •2+ which is planar, presumably due to the presence of the BF4 − counter-ion which interacts with both imine nitrogen atoms. Upon deprotonation of HL to form KL, an intense band at 654 nm appears ( Figure 5), and is similar, although red-shifted, to the HOMO-LUMO transition in related dipyrromethene compounds; [6] the band seen at 295 nm is indicative of re-protonation of KL and highlights its sensitivity to water. Oxidation of KL to the radical L • results in a considerable hypsochromic shift of the low-energy absorption band, from 654 to 456 nm, which is explained by an increase in the SOMO ( While the cyclic voltammogram (CV) of HL displays a single irreversible reduction at Ep c -1.46 V versus ferrocene ( Figure S11), the CV of KL consists of two reversible events, with an oxidation at -0.12 V and a reduction at -1.33 V (Figure 6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation